PENERAPAN PENDIDIKAN KARAKTER DI SDN 06 PANGKALAN KECAMATAN KOTO BARU KABUPATEN LIMA PULUH PROVINSI SUMATERA BARAT - MULIANI, RAUDATI (Jurnal Ilmu-Ilmu Sejarah, Budaya Dan Sosial ( LENTERA ), 2014)
With the character education applied systematically and sustainably, in school a childwill be emotionally intelligent. Emotional intelligence is an important provision in preparingchildren for the future, because one would be easier and successfully face all kinds of challengesof life, including the challenge to succeed academically.There are nine pillars of character that comes from universal noble values, namely: first, thecharacter of the love of God and all His creation; second, self-reliance and responsibility; Third,honesty / trust, diplomatically; fourth, respectful and polite; fifth, generous, like mutual help andcooperation / collaboration; sixth, confident and hardworking; seventh, leadership and fairness;eighth, kind and humble, and; ninth, the character of tolerance, peace, and unity.Keywords: Application of Character Education in